Rear Admiral Richard E. Byrd, 1936 - Hutchison, Ralph Raymond (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1936)
Rear Admiral Richard E. Byrd in his Hotel Washington room in downtown Pullman with two students, Joy Ellingson and Joan Wickersham. Byrd delivered afternoon and evening talks to capacity houses in Bryan Hall about his Antarctic expeditions.